Lattice and continuum based modeling of 2D materials - Sondipon Adhikari (Synthesis, Modeling, and Characterization of 2D Materials, and Their Heterostructures, 2020)
Hexagonal lattice–like structural forms are present in the nanostructures of several two-dimensional materials. The effective mechanical properties of these materials can be expressed on the basis of an equivalent continuum-based assumption. We focus on nanoscale analysis of the structures of such materials in this chapter based on a generalized analytical approach leading to closed-form formulae for the elastic moduli. Two different classes of single-layer materials (monoplanar and multiplanar) from a structural point of view are considered to demonstrate the results using these analytical formulae. The physics-based high-fidelity analytical models presented in this chapter are capable of obtaining the elastic properties in a computationally efficient manner for wide range of materials with hexagonal nanostructures.